Growth performance of the early life stages of broad-nosed pipefish, Syngnathus typhle (L.) fed different live or frozen diets - Correia, Miguel (2017)
This work tested the effect of using different live and frozen feed on the growth performance of Syngnathus typhle. It was divided into two experiments. In Experiment I Artemia and Atlantic ditch shrimp (Palaemonetes varians) larvae were used as live diets, whilst in Experiment II frozen mysids Mesopodopsis slabberi and frozen P. varians were used. At the end of the first experiment juvenile pipefish grew significantly more when fed P. varians (P < 0.05) with an overall Weight Gain (WG) of 914.8 +/- 79.3% bw day(-1), compared to Artemia fed fish (WG = 683.2 +/- 14.7%). Both mean Specific Growth Rate (SGR) and survival were similar between dietary treatments and did not vary significantly (P > 0.05). In Experiment II juveniles were weaned with frozen diets but no significant differences were found between the two tested diets in all parameters tested. Final WG was 516.5 +/- 63.3% and 566 +/- 17.6%, and Feed Conversion Ratio (FCR) was 30 +/- 1.5% and 28.2 +/- 1.2% for animals fed P. varians and M. slabberi respectively. Results indicate that P. varians is an adequate diet to use during initial stages of the S. typhle life cycle and should be considered as a frozen diet for subsequent life stages of this species as an alternative to currently known natural diets.